The Caspian Basin: Legal, political and security concerns, pipeline diplomacy and implications for EU energy security - Anis H. Bajrektarevic (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2015)
Regions, rich in energy resources, continue to be of crucial interest for our carbon-powered world. There are numerous things at stake to begin with, from international legal status, ownership rights, energy routes, transit corridors, state and corporate interests, environmental hazards and the overall puzzle of energy diplomacy. Additionally, Caspian is troubled with its own specific set of complexities that are listed in this work. They range from the undefined legal status, territorial disputes, ethnic instabilities and vicinity to other hot spots, such as the turmoil Middle East and the more recently sparked conflict in Ukraine. Besides the current and ongoing political, legal and security concerns, another layer of complexity represents the recent economic crisis and the steep fall in global energy prices. Caspian is already experiencing the negative effects of these trends, not to forget the implications of the crisis in the Russian Federation's economic and currency sectors and the overall decline of investments in the region over the past two years. In addition to recouping the losses from energy trade, important consequence will therefore be a much tougher competition to attract investments in the future, inevitably resulting in greater concessions made on the invested side which is likely to impact regional stability. Because of its geographical setting, the Caspian is also of central interest for the European energy security, although the supply chain from the region has been traditionally kept under Russian Federation control. However, for the past decade or so, the EU is becoming increasingly ambitious in planning Caspian pipelines that exclude Russian Federation's territory and the Nabucco Pipeline project was in the centre of these strategic efforts for a considerable amount of time. The Caspian is therefore also at a crossroads between grand and conflicting energy interests of Russian Federation and the Western Europe.
Keywords: K32; Q4; 330; Caspian water plateau; geo-economic passions and imperatives; riparian states; hydrocarbons; energy security